2021
DOI: 10.1371/journal.pone.0259139
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for COVID-19: Household food insecurity and vulnerability to shocks in Nairobi, Kenya

Abstract: An understanding of the types of shocks that disrupt and negatively impact urban household food security is of critical importance to develop relevant and targeted food security emergency preparedness policies and responses, a fact magnified by the current COVID-19 pandemic. This gap is addressed by the current study which draws from the Hungry Cities Partnership (HCP) city-wide household food insecurity survey of Nairobi city in Kenya. It uses both descriptive statistics and multilevel modelling using General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 29 publications
5
31
0
1
Order By: Relevance
“…The results showed that the head's gender was directly associated with food security and dietary diversity during the COVID-19 pandemic. Other scholars have also reported a female-headed households were more likely prone to food insecurity ( 59 ). The female-headed households faced challenges such as lower-income, limited access to capital, land ownership, market, and new technologies ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results showed that the head's gender was directly associated with food security and dietary diversity during the COVID-19 pandemic. Other scholars have also reported a female-headed households were more likely prone to food insecurity ( 59 ). The female-headed households faced challenges such as lower-income, limited access to capital, land ownership, market, and new technologies ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 98%
“…Household heads put the food security situation of the family in a favorable position through the income from the income-generating activities. Some studies have shown a direct relationship between the income of household heads (in the agricultural and nonagricultural sectors) and food security ( 59 , 69 – 71 ). High-income household heads are more likely to use food-based coping strategies during the COVID-19 epidemic to improve household nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The primary asset that ameliorates the food insecurity of urban households is urban-rural social networks since migrants to cities do not generally or immediately cut their links with rural homes. Food transfers and food remittances from rural areas are particularly important for food-insecure urban households (Onyango et al, 2021). There is evidence that urban households in Africa rely to varying degrees on an informal, non-marketed supply of food from their rural (and urban) relatives in order to survive within hostile urban environments.…”
Section: Migrationmentioning
confidence: 99%
“…19 Pre-pandemic data found 29% of households in Nairobi to be completely food insecure, with economic shock due to loss of employment as the main driver of food insecurity, highlighting concerning impacts of COVID-induced widespread job loss on households. 21 …”
Section: Introductionmentioning
confidence: 99%